Electronic strong coupling modifies the ground-state intermolecular interactions in self-assembled chlorin molecules - Subha Biswas; Mainak Mondal; Gokul Chandrasekharan; Kavya S. Mony; Akshay Singh; Anoop Thomas (Nature Communications)
Abstract The strong coupling of a molecular electronic transition with a quantized radiation field can result in modified photophysics compared to its uncoupled counterparts. Often, such changes are attributed to kinetic factors, overlooking the possible modifications to intermolecular interactions. The spin-cast films of chlorin e6 trimethyl ester (Ce6T) show an excitonic coupling band in absorption resulting from their ground-state intermolecular interactions and subsequent excimer-like emission upon photoexcitation. Interestingly, the electronic strong coupling (ESC) of the Ce6T Soret and Q-band suppresses the intermolecular excitonic interactions that otherwise exist in the Ce6T thin films and brings back the monomer-like emission characteristics. Our experiment provides a unique tool to tune the molecular assembly without involving chemical modifications. Our results suggest that ESC can induce modification to the intermolecular interaction forces that hold together the molecular assemblies in the ground state, which is a significant step toward understanding the fundamentals of polaritonic chemistry in detail.